THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND GOVERNMENT POLICY ON ENTREPRENEURIAL INTENTIONS WITH ATTITUDE AS AN INTERVENING VARIABLE (STUDY ON ISLAMIC BOARDING SCHOOL STUDENTS IN BANYUWANGI) - Fitriastuti, Dyah Ayu; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (IJBLE Scientific Publications Community Inc., 2023)
The phenomenon of students in Islamic boarding schools having an independent character has become a very interesting discussion in recent weeks. The santripreneur program is the realization of the Indonesian government's strategic efforts to develop entrepreneurial character while increasing the number of new entrepreneurs graduating from Islamic boarding schools. The urgency of this research is the development of Islamic boarding schools which have quite a big opportunity to develop an economic system in the Banyuwangi area. This research is a novelty and innovative since it conducts a thorough investigation to close the gaps left by earlier studies. The study's foundation is the Darul Anwar Banyuwangi Islamic Boarding School. This study uses a quantitative approach. Number of students at Business and Marketing Vocational Schools in Banyuwangi. The research sample consisted of (1) santri who had taken an entrepreneurship course and (2) santri who had lived in the boarding school for more than two years. The sample size is 275. The results of the research show that entrepreneurship education can increase the desire for entrepreneurship, attitudes towards entrepreneurship, and government policies can increase the desire for entrepreneurship. The Variance Based SEM method, sometimes referred to as Partial Least Square (PLS), employs the Structural Equation Model (SEM)